SENSITIVITI KEPELBAGAIAN BUDAYA DALAM KALANGAN GURU SEKOLAH KEBANGSAAN PELBAGAI ETNIK - Omar, Hafzan; Haron, Zolkepeli; A, Khairol (JISPO Jurnal Ilmu Sosial dan Ilmu Politik, 2018)
The aim of this study is to identify the multicultural sensitivity among multi-ethnic teachers in the primary school in Hulu Langat Area, Selangor. This study looks at the multicultural sensitivity based on ethnicity, level of education, income level, the position at school and residence location. The research employs a survey model, a quantitative research method which uses a questionnaire instrument. Cluster random sampling technique was used for the determining the research sample. 8 schools were randomly selected from 54 schools. Respondent consists of three major ethnic groups mainly Malays, Chinese and Indians teachers were selected through stratified random sampling technique. A total of 350 samples were involved in this study. The data was analyzed using the IBM SPSS Statistics 23 software. Descriptive analysis was used to obtain the mean score and also the standard deviation for each characteristic studied ie ethnicity, level of education, level of income, the position at school and place of residence. The findings show that the multicultural sensitivity among primary school teachers based on ethnicity, level of education, income level, a position at school and residence were at a high level.